Professional and Spiritual Practices in Sustaining Mutqin Qur’anic Memorization - Sopian Kamil Muttaqin; Muhammad Aufa Ihsan; Muhammad Rifaldi; Aulia Rizki; Moh. Saddad Muhibbi; Wida Nurahmawati Agustina (Jurnal Pendidikan Islam, 2026)
In Islamic educational institutions worldwide, sustaining Mutqin (robust and precise) Qur’anic memorization remains a persistent challenge, particularly for Huffāzh (Qur’an memorizers) who assume professional roles with competing institutional responsibilities. This study aims to explore the lived experiences of Tahfiz Qur’an (TQ) teachers in achieving and sustaining Mutqin Qur’anic memorization within the context of pesantren-based professional practice. A qualitative phenomenological approach was employed, involving six TQ teachers from five Qur’an-based pesantren in West Java, Indonesia, with data collected through in-depth interviews and reflective narratives. The findings reveal that achieving Mutqin memorization begins with the formation of a strong spiritual and disciplinary foundation, culminating in formal memorization certification, and is sustained through structured daily murāja’ah practices integrated into pre-, during-, and post-work routines. Participants encountered personal, cognitive, and institutional constraints; however, they addressed these challenges through self-regulation strategies, including adaptive time management, use of audio recitation technologies, workload adjustment, and reinforcement of spiritual discipline. The study concludes that sustaining Mutqin memorization is not solely an individual achievement but a professionally mediated pedagogical practice shaped by institutional support and spiritual commitment. These findings imply that pesantren and Islamic educational institutions should strengthen professional development, workload policies, and structured memorization support systems to sustain Qur’anic mastery among TQ teachers.